2023
DOI: 10.3390/buildings13092308
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Freeze–Thaw Cycles on the Shear and Microstructural Characteristics of Compacted Silty Clay

Jia Jia,
Hongying Wei,
Dehuan Yang
et al.

Abstract: The shear strength characteristics and weakening effect of soils under freeze–thaw (FT) cycling are the key problems that should be solved to ensure the integrity of infrastructure construction in seasonally frozen soil areas. Thus far, however, the research on the mechanism of strength deterioration resulting from microstructural changes induced by FT cycles remains insufficiently comprehensive. To investigate the deterioration characteristics of the shear strength of seasonally frozen soils in FT cycles, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our preliminary studies showed that the change is not obvious after five freeze-thaw cycles. Therefore, the number of freeze-thaw cycles is five in this paper, but the decreasing trend of soil shear strength is in agreement with the findings of other researchers [33,34]. For bare soil in Figure 6a, the percentage of decrease gradually tends to level off when experiencing 3 to 5 freeze-thaw cycles, which is consistent with the previous research [35].…”
Section: Effect Of the Number Of Freeze-thaw Cycles On The Shear Stre...supporting
confidence: 92%
“…Our preliminary studies showed that the change is not obvious after five freeze-thaw cycles. Therefore, the number of freeze-thaw cycles is five in this paper, but the decreasing trend of soil shear strength is in agreement with the findings of other researchers [33,34]. For bare soil in Figure 6a, the percentage of decrease gradually tends to level off when experiencing 3 to 5 freeze-thaw cycles, which is consistent with the previous research [35].…”
Section: Effect Of the Number Of Freeze-thaw Cycles On The Shear Stre...supporting
confidence: 92%
“…The cohesion first increases and then decreases with the increasing freeze-thaw cycles. After 30 freeze-thaw cycles, the cohesion of the soil samples is 4.34 kPa (C85), 7.93 kPa (C90) and 11.76 kPa (C95) respectively, which are 71.4%, 60.1% and 54.4% lower than the soil samples without freeze-thaw cycles (The experimental results are the same as Jia research 30 ). The cohesion first increases because small-size soil particles and salt crystals accumulate into large www.nature.com/scientificreports/ soil aggregates that contain soil and salt during the short-term freeze-thaw cycles (< 7), which enhances the bond strength between particles.…”
Section: Cohesionmentioning
confidence: 74%